Parenting and Inclusive Education - Rogers, Chrissie. author. aut Link
XI, 189 p.
Keywords: This tells of twenty-four couples negotiating the emotional and practical journey of parenting their learning 'disabled' child. The author, a researcher, sociologist and mother of a learning disabled daughter, questions the weak inclusive education discourse and unpacks parents' narratives in relation to denial, disappointment and social exclusion.